The One Health Consortium: Design of a Phase I Clinical Trial to Evaluate M032, a Genetically Engineered HSV-1 Expressing IL-12, in Combination With a Checkpoint Inhibitor in Canine Patients With Sporadic High Grade Gliomas - Chambers, M. R.; Bentley, R. Timothy; Crossman, David K.; Foote, Jeremy B.; Koehler, Jey W.; Markert, James M.; Omar, Nidal B.; Platt, Simon R.; Self, D. Mitchell; Shores, Andy; Sorjonen, Donald C.; Waters, Alicia M.; et al. (Frontiers in Surgery, 2020)
Primary malignant brain tumors in the United States are estimated to occur at an incidence of 14.7 per 100,000 people with 10,000–15,000 new cases diagnosed annually. Malignant gliomas are the most common primary brain tumors in humans, accounting for approximately 30% of all primary central nervous system (CNS) tumors in adults. In children, CNS tumors account for approximately 25% of all childhood malignancies and are the leading cause of cancer-related morbidity and mortality. Incidence, treatment and outcome patterns in pet dogs with high-grade gliomas are similar to humans. The most malignant of these tumors have been refractory to limited treatment options despite aggressive treatment; outcomes are dismal with median survivals just over one year in humans and two months in dogs. Novel treatments are greatly needed and combination therapies appear to hold promise. This clinical protocol, a dose-escalating phase I study in dogs with sporadic malignant glioma, represents a first in comparative oncology and combination immunotherapy. The trial will evaluate M032, an Interleukin-12 expressing Herpes Simplex virus, alone and combined with a checkpoint inhibitor, Indoximod. Preclinical models support the safety of intracranial inoculation with M032 in mice and nonhuman primates. M032 is currently being tested in humans with high-grade malignant gliomas. Thus, in a novel fashion, both canine and human trials will proceed concurrently allowing a direct “head-to-head” comparison of safety and efficacy. We expect this viral oncolytic therapy to be as safe as it is in human patients and M032 to (a) infect and kill glioma cells, producing a virus and tumor cell antigen-rich debris field; (b) provide an adjuvant effect due to liberation of viral DNA, which is rich in unmethylated CpG sequences that “toggle” TLR-9 receptors; and (c) express IL-12 locally, stimulating induction of TH1 lymphocytes. The resultant immune-mediated anti-viral responses should, through cross-epitope spreading, translate into a strong response to tumor antigens. The ability to compare human and dog responses in real time affords the most stringent test of suitability of the dog as an informative model of human brain tumors. Subsequent studies will allow canine trials to properly inform the design of human trials.